(untitled) (Scientific Journal of Educational Management, Research and law, 2026)
This paper titled "Re-engineering Ethical and Values Education as a Tool for Promoting Labour Market Inclusivity and National Economic Development in Nigeria" explores the critical role of ethical and values education in shaping an inclusive and productive labour market that drives national economic development. It provides a conceptual overview of key constructs such as ethical and values education, labour market, economic development, and labour market inclusivity. The paper identifies indicators of how ethical and values education contributes to workforce inclusivity, such as integrity, respect for diversity, civic responsibility, and workplace ethics. Furthermore, the paper discusses strategic ways of re-engineering ethical and values education to align with national development goals, emphasizing on building employability soft skills that incorporate ethical and values education that widen access to quality jobs, setting standards that enhances productivity via ethical work cultures among others. The paper also highlights challenges facing effective implementation, including poor curriculum integration between education and the labour market, character mismanagement, wilful disobedience to values and ethical practices, socioeconomic inequalities and cultural barriers among others. In conclusion, the paper put forward actionable strategies such as modelling ethical leadership and governance within schools and the public sector, and fostering multi-stakeholder partnerships between educational institutions, industries, and government. These efforts are positioned as pivotal in creating a workforce equipped with the moral and professional competencies needed for inclusive economic progress in Nigeria.